A rare case of fungal corneal ulcer (Indian Journal of Case Reports, 2025)
We report an unusual case of pigmented corneal ulcer caused by Curvularia species in a 60-year-old farmer from Southeast Asia who presented with pain and redness with reduced vision in the right eye for the past 2 weeks. The examination revealed an ulcer in the paracentral region of the cornea with a feathery margin, heaped-up infiltrates, and pigment deposits on the ulcer. Stromal edema and Descemet membrane folds were present. A non-mobile hypopyon was present in the anterior chamber with a cataractous lens and normal dilated retina examination. The corneal scrapping was done under topical anesthesia and sent for potassium hydroxide mount, sabouraud dextrose agar (SDA) culture, and lactophenol cotton blue (LPCB). The SDA and LPCB revealed dematiaceous fungi favoring Curvularia lunata. He was started on oral and topical anti-fungal and anti-biotic, anti-glaucoma and Cycloplegic eye drops. On follow-up, the ulcer showed significant improvement minimal scarring, and hypopyon with no pigment deposits. Pigmented corneal ulcer is an unusual presentation of fungal keratitis. Timely recognition, investigations, and treatment by ophthalmologists are crucial in the management of fungal corneal ulcers as fungal culture results take a serious amount of time. Curvularia is an uncommon species causing pigmentary fungal keratitis and responded best with antifungals in our patient.